IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II DI SDN 1 KERTAMUKTI - Intan, Neneng Nur; Happy Karlina Marjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the effectiveness of Cooperative Learning models in improving the learning outcomes of second-grade students at SDN 1 Kertamukti, Garut Regency, in the subject of Pancasila Education. The background of this study is the low student participation and suboptimal learning achievement on the theme “Caring for the Environment.” To address this, three Cooperative Learning models Think-Pair-Share, Jigsaw, and Make a Match were implemented across three 70-minute sessions. The participants were 35 students (17 boys and 18 girls). The research employed a classroom action research approach with observation, assessment, and reflection. Various media were used, including worksheets, videos, and learning cards. Results showed a substantial improvement in student engagement, collaboration, and learning outcomes. The average test score increased from 67.4 (pre-test) to 84.2 (post-test), and 88.6% of students achieved the minimum mastery criteria. Additionally, students demonstrated improved responsibility, communication, and environmental awareness. Classroom dynamics also became more positive, with students actively participating and showing enthusiasm. Challenges such as dominant group members and passive students were resolved through effective classroom management and group rotation. Overall, the Cooperative Learning approach proved effective in fostering academic success and character development in lower primary education.